Pearl S. Buck and the Forgotten Holocaust of the Two-Ocean War - Gennero, Valeria (Review of International American Studies, 2014)
Valeria Gennero Università di Bergamo, Italy During the Second World War, Pearl S. Buck was both a successful novelist and an influential political organizer, involved in well-known campaigns against racism and imperialism. In January 1942 she published Dragon Seed, a novel which described the Japanese sack of Nanking in 1937 and engaged the issues of nationalism and male violence from a gendered perspective. Buck wrote the novel before the United States entered the war: she hoped to promote American awareness of the Chinese fight for freedom, knowing that the tragic events which took place in Nanking after the fall of the city were virtually unknown in the United States. I will argue that, despite its original propagandistic intent, Dragon Seed succeeds—as Buck’s novels often do—in problematizing the notion of national identity, foregrounding the sexual politics of war.